Effects of Praeruptorin A and Praeruptorin C, a Racemate Isolated from Peucedanum praeruptorum, on MRP2 through the CAR Pathway - Zhou, Xunian; Bi, Huichang; Jin, Jing; Niu, Lu; Cai, Dake; Deng, Rongrong; Li, Yuhua; Wang, Yongtao; Huang, Min (Planta Medica, 2013)
Praeruptorin A and praeruptorin C, racemic to each other, are main bioactive constituents of the species Peucedanum praeruptorum, traditionally used as a Chinese herbal medicine (also known as Bai-Hua Qian Hu). In the present study, the ability of praeruptorins A and C to activate the constitutive androstane receptor and induce human multidrug resistance-associated protein 2 expressions in HepG2 cells was investigated. The changes in mRNA level, protein expression, and transport activity of multidrug resistance-associated protein 2 were determined by quantitative real-time PCR, Western blot, and the CDF uptake assay, respectively. The effects of constitutive androstane receptor knockdown on multidrug resistance-associated protein 2 mRNA and protein expression were also measured by transient transfection of a specific constitutive androstane receptor siRNA. The results showed that praeruptorin A and praeruptorin C significantly induced the multidrug resistance-associated protein 2 mRNA and protein expression, and enhanced the transport activity of multidrug resistance-associated protein 2. A further study showed that mRNA and protein upregulation were attenuated by transient transfection of a specific constitutive androstane receptor siRNA, suggesting that the upregulation of multidrug resistance-associated protein 2 was mediated by the constitutive androstane receptor. Taken together, our findings indicate that praeruptorin A and praeruptorin C can significantly upregulate multidrug resistance-associated protein 2 expression via the constitutive androstane receptor-mediated pathway in vitro, and this should be taken as an herb-drug interaction.
Keywords: praeruptorin A; praeruptorin C; MRP2; constitutive androstane receptor; herb-drug interaction; Peucedanum praeruptorum; Umbelliferae